A near infrared fluorescent/ultrasonic bimodal contrast agent for imaging guided pDNA delivery via ultrasound targeted microbubble destruction1. Issue 11 (7th February 2015) - Yang, Yongbo; Wang, Jinrui; Li, Xiaoda; Lin, Li; Yue, Xiuli
<x xml:space="preserve">Abstract</x> MBs@QDs@PEI/pDNA was prepared to operate as a NIR/Ultrasound bimodal imaging guided platform for targeting delivery of pDNA by UTMD.